Clinical Outcomes Following Single vs. Multiple Vessel Living-Donor Kidney Transplantation: A Retrospective Comparison of 210 Patients - Garcia, Leonardo E.; Parra, Natalia; Gaynor, Jeffrey J.; Baker, Lauren; Guerra, Giselle; Ciancio, Gaetano (Frontiers in Surgery, 2021)
Background.The use of living-donor kidney allografts with multiple vessels continues to rise in order to increase the donor pool. This requires surgeons to pursue vascular reconstructions more often, which has previously been associated with a higher risk of developing early post-transplant complications. We therefore wanted to investigate the prognostic role of using live-donor renal allografts with a single artery (SA) vs. multiple arteries (MA) at the time of transplant. Methods.We retrospectively analyzed a cohort of 210 consecutive living-donor kidney transplants performed between January, 2008 and March, 2019, and compared the incidence of developing postoperative complications and other clinical outcomes between SA vs. MA recipients. Results.No differences were observed between SA (N=161) and MA (N=49) kidneys in terms of the incidence of developing a postoperative (or surgical) complication, a urologic complication, hospital length of stay, delayed graft function, estimated glomerular filtration rate at 3mo or 12mo post-transplant, and graft survival. Conclusions.The use of live-kidney allografts with MA requiring vascular reconstruction shows excellent clinical outcomes and does not increase the risk of developing postoperative complications or other adverse outcomes when compared with SA renal allografts.